Ecological observations on spittlebugs with emphasis on their occurrence in rice - Nilakhe, Shashank S. (Pesquisa Agropecuaria Brasileira, 2014)
A survey for spittlebugs in rice fields of the State of Mato Grosso do Sul showed presence of as many as 36 adults/10 sweeps of a sweep net. Spittlebug densities were also monitored in pastures and the adjoining rice fields. The observations in the rice were made from germination till flowering. The insects flew to rice despite the abundance of food and very low density (about 4 adults/10 sweeps) in pastures. The adults tended to invade rice in large numbers when the plants were about 20 cm or taller. At densities < 10 adults/10 sweeps, the counts tended to follow the negative binomial distribution and at higher densities the Poisson distribution. Spittlebugs preferred the rice field with taller rice plants rather than the adjoining rice field with shorter plants. In a screenhouse, the insects preferred pasture plants over rice and corn of the same height. Eggs of these insects were found in the rice fields. However, the nymphs were detected on extremely rare occasions.